Construction and levitation guidance experiment of magnetic levitation system without gap sensors using inductance model of thin steel plates. Issue 3 (31st December 2018) - Odajima, Yusuke; Takada, Yusuke; Oikawa, Ikuto; Nakagawa, Toshiko
Abstract: Recently, the noncontact conveyance methods that are applied magnetic levitation techniques have been studied in many institutes. In this paper, from the view point of practical use, the authors construct a magnetic levitation system without using gap sensors which have been essential for the conventional magnetic levitation of thin steel plates. This system adopts both current sensors and Hall‐effect sensors in place of the gap sensors. In addition, we consider the peculiar inductance characteristics of magnetic levitation for a thin steel plate. Moreover, we conduct the levitation, guidance, conveyance and disturbance experiments.